An embedded environment sensing device based on the ARM processor - Lek, Annabella Szer Miang (2017)
Compared to other countries around the globe, Singapore is a small and relatively densely populated one with an average of 7,829 residents per square kilometres of land area. However, as we become more urbanized and densely populated, noise cannot be avoided nor overlooked as it affects the quality of our daily lives.